PENGEMBANGAN GAMES EDUKASI BERBANTUAN WORDWALL PADA MUATAN IPAS TOPIK KEKAYAAN BUDAYA INDONESIA KELAS IV SEKOLAH DASAR NEGERI 41 PONTIANAK UTARA - Nurhamzah, Dede; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
In general, this research aims to develop educational games on wordwall website for IPAS learning content at 4th grade class at SD Negeri 41 Pontianak Utara wich is eligible to assist learning activities in Merdeka Curriculum. The present study utilizes the RD (Research and Development) method, employing the ADDIE model. The data of research was obtained form one class at SD Negeri 41 Pontianak Utara, totaling 27 students, and assisted by 2 validators consisting of an expert of media and an expert of material. The research also involved a 4th grade teacher. The techniques of collection of data are observation, interviews, and questionnaires. The findings of the study indicated that the development of wordwall educational games on IPAS learning content for the "Kekayaaan Budaya Indonesia" topic for grade IV demonstrated a high degree of validity, an average percentage of 95.38% in the media aspect category, and an average percentage of 96.66% in the material aspect category, both of which fall within the "Very Valid" category. The practicality level of the wordwall educational games was determined to be "Very Practical" based on the responses of the student questionnaires, with an average percentage of 94.59%. Similarly, the responses from the teacher questionnaires yielded an average percentage of 95.38%, also categorizing the wordwall educational games as "Very Practical."In conclusion, the developed media has been determined to be both viable and practical for utilization in classroom learning activities, as substantiated by the aforementioned results.